Mechanism of NMDA receptor channel block by MK-801 and memantine - Song, Xianqiang (Nature, 2018)
The N-methyl-D-aspartate (NMDA) receptor transduces the binding of glutamate and glycine into the opening of a calcium-permeable ion channel(1). Because the NMDA receptor has proven recalcitrant to high resolution structural studies, the mechanism by which ion channel blockers occlude ion permeation is not well understood. Here we show that removal of the ATD domains from the GluN1/GluN2B NMDA receptor (∆ATD) yields a functional receptor and well diffracting crystals, allowing us to map the binding site of the iconic NMDA receptor blocker, MK-801. Together with long-timescale molecular dynamics simulations, we illustrate how MK-801 and memantine, a drug approved for the treatment of Alzheimer’s disease, bind within the ion channel vestibule, promote closure of the ion channel gate and lodge between the M3 helix bundle crossing and the M2 pore loops, physically blocking ion permeation.